Significance of Literacy in Inclusive Growth and Coherent Development Planning to Deal with Challenge of Quality Education for All in Pakistan - Siddiqui, Mazhar Ali; Tagar, Hamzo Khan (Archives of Business Research, 2018)
The study focused on the strategic planning to achieve the sustainable development goal 4 quality education for all in context of Pakistan where more than forty percent people are illiterate and females are more than that, it examines the major obstacles in the system to improve as per need of the hour to develop innovative approach for improvement in schooling system particularly in Pakistan and generally in developing world because problems are mostly same in their nature and structure. It finds that development allocation fared poorly in the past for education development in the region, lower literacy rate strengthen feudalism and contributing to unskilled- or semi-skilled labour which is spreading poverty and inequality in the country. Above all social ill also spreads negative approach like street crime terrorism, slow and unstable economic growth. Weakened Governance, Poor Quality of Teachers & Managers needs to improve, Quality of curriculum, textbooks & exams, out of school children, steady dropouts, In-adequate financing, Gender discrimination’s, Poor monitoring & evaluation, Imbalance in primary, middle & secondary schools, Low Incentives and teacher’s manager tussles are the major obstacles of the schooling system which impacted as low literacy and poor quality. Above mentioned issues direly need to adopt an innovative approach to tackle all obstacle’s in decent manners and through coherent development planning, policies and practices within the political economy frame work due to growth and literacy nexuses in larger public interest to bring quality educations for all in Pakistan within due course of time.